Pitcairnia anarosae (Bromeliaceae; Pitcairnioideae) a new species from the state of Oaxaca, México - Mejía-Marín, María Isabel; González-Rocha, Edith; Espejo-Serna, Adolfo (Phytotaxa, 2020)
Pitcairnia anarosae, known until now from the municipality of San Juan Colorado, Oaxaca, Mexico, is described and illustrated. The new species is compared with P. singularis, from which differs by the plant height (19–40 vs 15–25 cm) the number of leaves (5–8 vs 3–4), and the morphology, color (red vs white) and length of flowers.